Determinants of physical and global functioning in adult HIV-positive heterosexual men. - Shah, Krupa; McMahon, James M; Trabold, Nicole; Aidala, Angela A; Chen, Michael; Pouget, Enrique R; Simmons, Janie; Klostermann, Keith (AIDS care, 2015)
Little is known about the psychosocial factors that might impact the functioning ability of heterosexual men living with HIV. We examined positive and negative coping, social support, and HIV stigma as predictors of physical and global functioning in a cross-sectional sample of 317 HIV-infected adult heterosexual male patients recruited from clinical and social service agencies in New York City. Study participants were primarily minority and low income. Sixty-four percent were African-American, 55% were single, and 90% were 40 years of age or older. The majority had long-term HIV (LTHIV), with an average duration of 15 years since diagnosis. After controlling for participant characteristics, structural equation modeling analyses revealed that positive coping and social support had a significant positive direct effect on global functioning, while stigma had a significant negative direct effect on global functioning. The physical functioning model revealed that negative coping and HIV stigma had significant negative direct effects, whereas social support had a significant positive indirect effect. Age and duration of HIV diagnosis were not associated with physical and global functioning. In conclusion, we found that heterosexual men living with LTHIV who have ineffective coping, less social support, and greater stigma have reduced functioning ability. Study findings have implications for developing interventions aimed at increasing and retaining functioning ability with the end goal of improving successful aging in this population.